Comparative study of the three-dimensional genomes of granulosa cells in germinal vesicle and metaphase II follicles - Mao, Rurong; Cai, Zhongkun; Wang, Tao; Li, Yan; Tian, Shilin; Li, Diyan; Li, Penghao (Frontiers in Genetics, 2024)
IntroductionFollicle development is a critical process in the female reproductive system, with significant implications for fertility and reproductive health. Germinal vesicle (GV) oocytes are primary oocytes that are arrested in the dictyate stage, also known as the diplotene stage of meiotic prophase I. Metaphase II (MII) is the stage at which the oocyte is typically retrieved for assisted reproductive technologies such as in vitro fertilization (IVF). The granulosa cells play a pivotal role in follicle development processes. 3D chromatin organization is a fundamental aspect of cellular biology that has significant implications for gene regulation and cellular function.MethodsIn this study, we investigated 3D chromatin organization in granulosacells from GV and MII follicles, which is essential for understanding the regulatory mechanisms governing oocyte development.ResultsThe results revealed distinct compartmentalization patterns,including stable genomic regions and transitions during oocyte maturation. Notably, there was a significant shift in functional gene activation, particularly in processes related to hormone metabolic pathways. Furthermore, alterations in topologically associating domains (TADs) were observed, with differential expression observed in genes that are involved in crucial biological processes. The analysis also identified a subset of genes with altered promoter-enhancer interactions (PEIs), reflecting a regulatory shift in gene expression related to reproductive processes.DiscussionThese findings provide valuable insights into 3D genome organization in granulosa cells with implications for reproductive health and the development of assisted reproductive technologies. Understanding spatial genome organization at different stages of follicular development may help realize novel strategies for enhancing success rates in assisted reproductive technologies.